2010
DOI: 10.1002/jbmr.163
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin induces osteogenic differentiation of murine embryonic stem cells

Abstract: Statins are potent inhibitors of cholesterol synthesis. Several statins are available with different molecular and pharmacokinetic properties. Simvastatin is more lipophilic than pravastatin and has a higher affinity to phospholipid membranes than atorvastatin, allowing its passive diffusion through the cell membrane. In vitro studies on bone marrow stromal cells, osteoblast-like cells, and embryonic stem cells have shown statins to have cholesterol-independent anabolic effects on bone metabolism; alas, statin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 42 publications
(77 reference statements)
2
51
0
Order By: Relevance
“…Doses employed in this study were similar to those reported previously, since simvastatin dosed at 10 À6 to 10 À9 M had already been tested on MC3T3-E1 cells by other investigators [4,11]. It should be noted that the use of higher doses of statins was previously shown to yield a negative effect on cell viability [12].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Doses employed in this study were similar to those reported previously, since simvastatin dosed at 10 À6 to 10 À9 M had already been tested on MC3T3-E1 cells by other investigators [4,11]. It should be noted that the use of higher doses of statins was previously shown to yield a negative effect on cell viability [12].…”
Section: Discussionmentioning
confidence: 84%
“…However, there could be variations in doses to achieve the maximal effect, depending on the system model, the stage of differentiation of osteoblasts, and the culturing time period [2,14]. Moreover, simvastatin can induce murine embryonic stem cell (mESC) differentiation toward the osteogenic lineage in the absence of osteoinductive supplements, according a recently published report [12].…”
Section: Discussionmentioning
confidence: 96%
“…In this context, the activation and differentiation of DPSC may function positively for dentin regeneration. Recently, it has been reported that simvastatin (ST) has the potential to induce osteoblastic bone formation or enhance the expression of bone morphogenetic protein (BMP)-2 for several osteogenic cells [6][7][8] . Some investigators have demonstrated that DPSC can be differentiated into odontoblasts by BMP-2, resulting in the promotion of dentin formation [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…The majority of osteogenic protocols for ESCs direct cell differentiation by including factors in the culture medium, such as b-glycerophosphate (BGP), ascorbate, dexamethasone, simvastatin, retinoic acid, vitamin D 3 , and bone morphogenic proteins [3,[22][23][24][25][26][27][28][29][30]. Although traditional osteogenic differentiation strategies for ESCs leads to the formation of bone nodules and expression of osteogenic markers, little research has compared this to the in vitro differentiation of osteoblasts.…”
mentioning
confidence: 99%